2003
DOI: 10.1016/s0896-6273(03)00459-8
|View full text |Cite
|
Sign up to set email alerts
|

Stereopsis Activates V3A and Caudal Intraparietal Areas in Macaques and Humans

Abstract: Stereopsis, the perception of depth from small differences between the images in the two eyes, provides a rich model for investigating the cortical construction of surfaces and space. Although disparity-tuned cells have been found in a large number of areas in macaque visual cortex, stereoscopic processing in these areas has never been systematically compared using the same stimuli and analysis methods. In order to examine the global architecture of stereoscopic processing in primate visual cortex, we studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

52
333
3
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 325 publications
(391 citation statements)
references
References 70 publications
52
333
3
3
Order By: Relevance
“…The correspondence between fMRI activation patterns in monkeys and humans in previous studies (e.g., [53][54][55][56][57][58] and, partly, in our work is encouraging, although it does not necessarily imply that the underlying behavioral strategies and neuronal activity in the two species are the same. Nevertheless, monkey fMRI provides a crucial control for the common interpretation of human imaging and monkey electrophysiology data.…”
Section: Discussionsupporting
confidence: 73%
“…The correspondence between fMRI activation patterns in monkeys and humans in previous studies (e.g., [53][54][55][56][57][58] and, partly, in our work is encouraging, although it does not necessarily imply that the underlying behavioral strategies and neuronal activity in the two species are the same. Nevertheless, monkey fMRI provides a crucial control for the common interpretation of human imaging and monkey electrophysiology data.…”
Section: Discussionsupporting
confidence: 73%
“…Two juvenile (4 -6 kg) male rhesus monkeys (M. mulatta) were used in the monkey fMRI experiments. Surgical details and the training procedure have been described (8,45,46) and are summarized here. Each monkey was implanted with an MRI-compatible plastic headset.…”
Section: Methodsmentioning
confidence: 99%
“…In agreement with its various roles, disparity activates many brain regions in monkeys and humans (e.g., Janssen et al, 2000b;e.g., Ferraina et al, 2000;Parker, 2007;Preston et al, 2008;Georgieva et al, 2009). Studies using functional magnetic resonance imaging (fMRI) in rhesus monkeys have shown that disparity activates regions in the dorsal visual stream (Tsao et al, 2003b;Durand et al, 2007), frontal cortex (Joly et al, 2009), and early ventral stream (Tsao et al, 2003b). However, no fMRI study has described clear disparity activation in anterior parts of the ventral visual stream, including inferior temporal cortex (IT), a part of cortex thought to be important in object vision.…”
Section: Introductionmentioning
confidence: 99%